Motivational climate towards sport according to gender, degree and level of physical activity in undergraduate students of Education - Jerez López, Pablo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
During the past years, the practice of physical activity has turned into a necessary way to improve our health, due to it, many authors have studied some factors which can intercede in its fulfilment. This descriptive and cross-sectional research was conducted on a sample of 571 undergraduate students of Education Faculty the University of Granada. The purpose of this study is to analyse the motivational climate and its relation with socio-demographic aspects such as sex, degree and level of physical activity, using as main instrument the PMSCQ-2 questionnaires. The results showed that male participants are associated to higher marks on Ego Climate, as well as being a Social Education student is related to a bigger Task Climate orientation. The practice of physical activity also affects the Task Climate and encourages team work. In short, this research has demonstrated that motivation affects positively to Task Climate and negatively to Ego Climate, verifying also some differences owing to the age of the participants.